Primary Sarcoma of Descending Aorta - Tessitore, Adele; Mariolo, Alessio V.; Galetta, Domenico; Sedda, Giulia; Spirito, Rosa; Spaggiari, Lorenzo (AORTA, 2019)
Primitive aortic sarcomas are rare tumors characterized by resistance to medical treatment and a poor prognosis with high metastatic rates and local recurrences. Surgery remains the mainstay treatment and is based on challenging and technically demanding resections with high rate of major intraoperative and postoperative complications. We report the case of a patient with primitive intimal sarcoma of the aorta, who underwent a descending aortic resection and reconstruction with a prosthetic tube.
Keywords: intimal sarcoma; aorta reconstruction; descending aorta